Down-Regulation of Inpp5e Associated With Abnormal Ciliogenesis During Embryonic Neurodevelopment Under Inositol Deficiency - Yue, Huixuan; Li, Shen; Qin, Jiaxing; Gao, Tingting; Lyu, Jianjun; Liu, Yu; Wang, Xiuwei; Guan, Zhen; Zhu, Zhiqiang; Niu, Bo; Zhong, Rugang; Guo, Jin; et al. (Frontiers in Neurology, 2021)
The inositol polyphosphate-5-phosphatase E (Inpp5e) gene is located on chromosome 9q34.3. The enzyme it encodes mainly hydrolyzes the 5-phosphate groups of phosphatidylinositol (3,4,5)-trisphosphate (PtdIns (3,4,5) P3) and phosphatidylinositol (4,5)-bisphosphate (PtdIns (4,5) P2), which are closely related to ciliogenesis and embryonic neurodevelopment, through mechanisms that are largely unknown. Here we studied the role of Inpp5e gene in ciliogenesis during embryonic neurodevelopment using inositol-deficiency neural tube defects (NTDs) mouse and cell models. Confocal microscopy and scanning electron microscope were used to examine the number and the length of primary cilia. The dynamic changes of Inpp5e expression in embryonic murine brain tissues were observed during Embryonic Day 10.5-13.5 (E 10.5-13.5). Immunohistochemistry, western blot, polymerase chain reaction (PCR) arrays were applied to detect the expression of Inpp5e and cilia-related genes of the embryonic brain tissues in inositol deficiency NTDs mouse. Real-time quantitative PCR (RT-qPCR) was used to validate the candidate genes in cell models. The levels of inositol and PtdIns(3,4)P2 were measured using gas chromatography-mass spectrometry (GC-MS) and enzyme linked immunosorbent assay (ELISA), respectively. Our results showed that the expression levels of Inpp5e gradually decreased in the forebrain tissues of the control embryos, but no stable trend was observed in the inositol deficiency NTDs embryos. Inpp5e expression in inositol deficiency NTDs embryos was significantly decreased compared with the control tissues. The expression levels of Inpp5e gene and the PtdIns(3,4)P2 levels were also significantly decreased in the inositol deficient cell model. A reduced number and length of primary cilia were observed in NIH3T3 cells when inositol deficient. Three important cilia-related genes (Ift80, Mkks, Smo) were down-regulated significantly in the inositol-deficient NTDs mouse and cell models, and Smo was highly involved in NTDs. In summary, these findings suggested that down-regulation of Inpp5e might be associated with abnormal ciliogenesis during embryonic neurodevelopment, under conditions of inositol deficiency.